MARKETING STRATEGY OF STUDENTS PERCEPTION TO SAVE IN SYARIAH BANKING AT SRIWIJAYA UNIVERSITY PALEMBANG (Strategi Pemasaran Terhadap Persepsi Mahasiswa Untuk Menabung Di Bank Syariah Pada Universitas Sriwijaya Palembang) - Delta Khairunnisa (Jurnal Ilmiah Econosains, 2014)
ABSTRACTThis research entitled Marketing Strategy of Students Perception to save in Syariah Banking at Sriwijaya University Palembang was aimed at investigating and analyzing whether mixed marketing variables altogether affected students decision on whether or not to save at Syariah Banking, and to investigate which factors that were the most dominant. This research was a causal research which used two groups of variables. They were independent variables consisting of product (X1), price (X2), place (X3), promotion (X4), people (X5), process (X6), and customer service (X7). The dependent variables was students perception (Y) toward to service of syariah banking which consisted of expectation, motivation, and learning. To measure relationship among variables, multiple regression statistical analysis was used. Based on the resultsof regression analysis, all mixed marketing variables altogether affected students’ decision making in whether or not saving at syariah banking. Partially, variables of product, promotion and customer service had dominant affects toward students’ decision on saving at syariah banking.Keywords : Marketing Strategy, Marketing Mix, Perception, Syariah Banking